Manifestasi Klinis Infeksi Human Papillomavirus di Bidang Dermatology dan Venereology - Yuli Wahyu Rahmawati; Yelvi Levani; Musa Ghufron; Maya Rahmayanti (Jurnal Keperawatan Muhammadiyah, 2020)
Objective:  To provide information about clinical manifestation human Papillomavirus infection  Methods: This article is literature review. The searching method used  pubmed database from last 10 years. Review: Human Papillomavirus infection is caused by Papillomaviridae, it made proliferation mucosa epitel and skin. More than 100 genotype viral has been identified, human Papillomavirus strain was classification based on oncogenic and non oncogenic type. The diagnosis was based on clinical features, histopathology and molecular biology. Therapy human Papillomavirus infection was based on morfologi, distribution, account of lesion, choice of patient and skill of practitionerConclusion:  Patient with history of infection human Papillomavirus can be reccuren